2017
DOI: 10.1177/0009922817724399
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Pill-Swallowing Ability in Pediatric Patients

Abstract: Difficulty with pill-swallowing ability (PSA) is common in children, yet formal evaluation is rare. The objective of this study was to prospectively evaluate and compare PSA of inpatient and outpatient children using the Pediatric Oral Medications Screener. We identified children aged 3 to 17 years admitted to a general or subspecialty pediatric service at a university hospital or outpatient clinic. Using the Pediatric Oral Medications Screener, patients were observed swallowing 3 different-sized placebo pills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Some attempts have been made in paediatric studies such as that of Jones et al, who state the dimensions of placebos and Rashed et al who used sweets and cake decorations of equivalent sizes to licensed medicines to aid “pill swallowing training”. 35 , 49 A reporting consensus needs to be reached in order to make valid comparisons and conclusions across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some attempts have been made in paediatric studies such as that of Jones et al, who state the dimensions of placebos and Rashed et al who used sweets and cake decorations of equivalent sizes to licensed medicines to aid “pill swallowing training”. 35 , 49 A reporting consensus needs to be reached in order to make valid comparisons and conclusions across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Taking this into account, a recent Japanese study declares that the ideal indices for tablet/capsule size is to consider length + width + height with a cut‐off acceptability of 21 mm. Some attempts have been made in paediatric studies such as that of Jones et al, who state the dimensions of placebos and Rashed et al who used sweets and cake decorations of equivalent sizes to licensed medicines to aid “pill swallowing training” 35,49 . A reporting consensus needs to be reached in order to make valid comparisons and conclusions across studies.…”
Section: Discussionmentioning
confidence: 99%
“…106 In another trial involving HIV-infected children, most children were capable of switching from syrup to scored adult-dose tablets of combination antiretroviral medicines at about 3 years. 107 Furthermore, there is accumulating evidence that some children aged 2-5 years can swallow tablets, and even capsules 65,66,68,108 (Table 8). More recently, Bracken et al have shown that tablets of 6-10 mm in size are potentially acceptable formulation for children aged 4-12 years.…”
Section: Conventional Tablets Capsules and Scored Tabletsmentioning
confidence: 99%
“…1 However, inability to swallow tablets and capsules is a common issue in young children. 2,3 In one study, as few as 25%-45% of patients aged 4 to 7 could swallow solid dosage forms, with the ability to do so improving at older ages. 2 Nonetheless, patients as young as 4 to 5 years old can learn to swallow tablets with training and, in one study, learned more quickly than older children.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In one study, as few as 25%-45% of patients aged 4 to 7 could swallow solid dosage forms, with the ability to do so improving at older ages. 2 Nonetheless, patients as young as 4 to 5 years old can learn to swallow tablets with training and, in one study, learned more quickly than older children. 4 There have been recent efforts to understand and improve approaches to oral dosing in paediatric populations, 5,6 but little has been reported in children with progressive neuromuscular disorders who have muscle weakness and impaired motor ability, including oral motor activity.…”
Section: Introductionmentioning
confidence: 99%